Socio-Economic Determinants of China’s Recent Economic Growth - Kim, Sungwoo (Journal of Reviews on Global Economics, 2014)
Â This paper analyzes various socio-economic aspects of China and Japan in order to identify the major determinants for China’s recent ascendancy over Japan as the world’s second largest economy. Those aspects considered include China’s aggressive policies for promoting exports, including high tech, capital formation, foreign direct investments, research and development, and tertiary education. China’s economic growth also generated several serious adverse effects, such as income inequity, import of energy resources, environmental degradation, and international tension in the South China Sea, which may become serious bottlenecks for China’s future economic growth.